Adequacy of test standards in evaluating blast overpressure (BOP) protection for the torso - Whyte, Tamlin (Cranfield University, 2016)
The blast wave emanating from an explosion produces an almost instantaneous rise in pressure which can then cause Blast Overpressure (BOP) injuries to nearby persons. BOP injury criteria are specified in test standards to relate BOP measurements in a testing environment to a risk of BOP injury. This study considered the adequacy of test standards in evaluating BOP protection concepts for the torso. Four potential BOP injury scenarios were studied to determine the likelihood of injury and the adequacy of test standards for appropriate protection concepts. In the case of vehicle blast, BOP injury is unlikely and test standards are adequate. In the scenario involving an explosive charge detonated within a vehicle, and the close proximity to a hand grenade scenario, test standards are not available. The demining scenario was identified as of importance as test standards are available, but do not mandate the evaluation of BOP protection. A prototype South African Torso Surrogate (SATS) was developed to explore this scenario further. The SATS was required to be relatively inexpensive and robust. The SATS was cast from silicone (selected to represent body tissue characteristics) using a torso mould containing a steel frame and instrumented with chest face-on pressure transducer and accelerometer. The SATS was subjected to an Anti-Personnel (AP) mine test and the Chest Wall Velocity Predictor and Viscous Criterion were used to predict that BOP injuries would occur in a typical demining scenario. This result was confirmed by applying the injury criteria to empirical blast predictions from the Blast Effects Calculator Version 4 (BECV4). Although limitations exist in the ability of injury criteria and measurement methods to accurately predict BOP injuries, generally a conservative approach should be taken. Thus, it is recommended that the risk of BOP injuries should be evaluated in demining personal protective equipment test standards.